2006
DOI: 10.1271/bbb.60006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flavonoid 7-O-Glucosyltransferase fromArabidopsis thaliana

Abstract: Most flavonoids found in plants exist as glycosides, and glycosylation status has a wide range of effects on flavonoid solubility, stability, and bioavailability. Glycosylation of flavonoids is mediated by Family 1 glycosyltransferases (UGTs), which use UDP-sugars, such as UDP-glucose, as the glycosyl donor. AtGT-2, a UGT from Arabidopsis thaliana, was cloned and expressed in Escherichia coli as a gluthatione S-transferase fusion protein. Several compounds, including flavonoids, were tested as potential substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Because UGT has nucleotide sugar specificity, 50 UGTs from Oryza sativa, Glycine max, Bacillus subtilis, and Arabidopsis thaliana were screened to find a UGT that could use quercetin as a sugar acceptor and dTDP-6-deoxytalose as a sugar donor. Each UGT gene used had previously been subcloned into the E. coli expression vector pGEX (8)(9)(10). Each UGT gene was transformed into BL21(DE3) containing pA-tll or the pACYCDuet vector, and the biotransformation of quercetin by each transformant was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because UGT has nucleotide sugar specificity, 50 UGTs from Oryza sativa, Glycine max, Bacillus subtilis, and Arabidopsis thaliana were screened to find a UGT that could use quercetin as a sugar acceptor and dTDP-6-deoxytalose as a sugar donor. Each UGT gene used had previously been subcloned into the E. coli expression vector pGEX (8)(9)(10). Each UGT gene was transformed into BL21(DE3) containing pA-tll or the pACYCDuet vector, and the biotransformation of quercetin by each transformant was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…UGT genes from various sources were cloned into pGEX vector as described previously (8)(9)(10) and transformed into E. coli BL21(DE3), which was already transformed with pA-tll. As control, each UGT gene was transformed into E. coli BL21(DE3) containing empty pACYCDuet.…”
Section: Methodsmentioning
confidence: 99%
“…Various fungi have been proven to have the ability to convert structurally different foreign phenolics into their corresponding glycosides with high yields (17)(18)(19)(20)(21)(22). This glycosylation capability might be derived from the mechanism of self-protection from diverse xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
“…For example, xanthohumol is glycosylated by Absidia coerulea AM93, Rhizopus nigricans UFP701, and Beauveria bassiana AM446 (17,18); quercetin, kaempferol, and isorhamnetin can be converted to their glycosides by Cunninghamella elegans ATCC 9245 (19); and Trichoderma koningii KTCC 6042 glycosylates silybins A and B to silybin A 3-O-␤-glucopyranoside, silybin A 7-O-␤-glucopyranoside, silybin B 3-O-␤-glucopyranoside, and silybin B 7-O-␤-glucopyranoside, respectively (20,21). However, the genes encoding P-UGTs in fungi have not yet been identified.…”
mentioning
confidence: 99%
“…The dominant peak at 7.8 min was consistent with formation of quercetin 3-O-β-D-glucopyranoside ( Figure 3B). Although we could not determine the chemical structure of the minor peak at the retention time of 8.8 min, it has been reported that Arabidopsis UGT73B1 (At4g34138) catalyzes 7-O-glucosylation of quercetin (Kim et al 2006). UGT73A17 may be a bifunctional UGT forming quercetin 3-O-β-D-glucopyranoside and quercetin 7-O-β-D-glucopyranoside The maximum velocity (V max ) and estimated apparent K m values of UGT73A17 with quercetin were determined to be 143.7±9.7 µmol min −1 mg −1 protein and 9.9±2.3 (μM), respectively.…”
mentioning
confidence: 87%